Odpowiedź :
Odpowiedź:
4x-4 = 2x+8
4x-2x= 8 +4
2x= 12 /:2
x= 6
spr.. 4*6 -4= 2*6 +8
24-4= 12+8
20=20
L=P
______________________
3 ( x-2) =x
3x-6= x
3x -x= 6
2x= 6 /:2
x=3
spr.. 3*3 -6 =3
9-6=3
3=3
L=P
__________________
5 ( x-1) = 3 x-3
5x -5 =3x-3
5x-3x= -3 +5
2x= 2 /:2
x=1
spr.. 5*1 -5 = 3*1 -3
5-5= 3-3
0=0
L=P
Szczegółowe wyjaśnienie:
4x - 4 = 2x + 8
4x - 2x = 8 + 4
2x = 12 |: 2
x = 6
3 (x - 2) = x
3x - 6 = x
-6 = x - 3x
-6 = -2x |: (-2)
3 = x
x = 3
5 (x - 1) = 3x - 3
5x - 5 = 3x - 3
5x - 3x = -3 + 5
2x = 2 |: 2
x = 1